Project GYM: A randomized feasibility study investigating effect on motivation of personal trainer‐led exercise in young men with hemophilia. Issue 8 (26th November 2021) - McLaughlin, Paul; Holland, Mike; Dodgson, Sandra; Khair, Kate
Abstract: Introduction: Many young men with hemophilia engage in physical activity and sport but face challenges to participation because of their hemophilia. Project GYM aimed to investigate the feasibility of a hemophilia‐specific fitness program led by a personal trainer (PT) and its impact on gym activity, motivation, and adherence to exercise. Methods: This was a nonblinded, randomized feasibility study, recruiting participants aged 18 to 25 years with hemophilia A or B (all severities, ± inhibitor) from three London hemophilia centers. All participants were given an activity tracker and free gym membership. Participants were randomized to a "gym only" or "gym and PT" arm. Participants completed questionnaires evaluating motivation to exercise, quality of life, physical activity levels, self‐efficacy, and self‐esteem at study start and study end. Results: Of 142 eligible individuals, 19 agreed to participate. Participants were healthy, with mean body mass index and adiposity slightly lower than the UK average. They reported low bleed numbers and had good joint health (median Hemophilia Joint Health Score [HJHS], 0; range, 0‐13). The gym and PT group had more gym attendance than the gym‐only group. Seven participants increased their activity levels and nine stayed the same, with no statistical difference between groups. HJHS scores improved in 3 participants and were unchanged in 12. There was no bleeding associated with gym activity. Conclusion: Project GYM has demonstrated the safety and feasibility of a tailored physical training program in young men with hemophilia. Increased gym attendance, with and without support from a PT, is associated with increased physical activity.